The Role Of Recording And Reporting Process Of Basic Accounting In Small Medium Enterprises Of Omah Duren Surabaya - Lucya Erlinda Sonia; Stefanie Gianto (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2018)
Financial management is a problem that is quite difficult for Small and Medium Enterprises (SMEs) in Indonesia. The lack of awareness and knowledge of SMEs owner regarding the accounting process considered as the root causes of their financial management difficulties. Based on that, researcher aims to help one of SMEs in Surabaya which is Omah Duren Surabaya, in order to know about the process of recording and reporting a SME, then find a way to improve it in a diligent way. Researcher uses interviews, observations and documents sheets to analyze and know-how Omah Duren business process. The information that gained from Omah Duren owner and transaction data, as well as direct observation in recording and reporting activities is one of researcher data sources. Researcher concluded that Omah Duren SME’s still not performing the simple accounting process in accordance with generally accepted. Therefore, researcher provide a recommendations in helping them in recording and reporting their financial effectively and efficiently. This research will also discuss the role of recording and reporting that is generally accepted for SMEs.